How to Develop Coastal Tourism? Evidence from Mataram City, Lombok - Yunia Ulfa Variana; M. Setyo Nugroho (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: The objective of this study is to establish a sustainable coastal tourism development framework in Mataram City that integrates environmental, socio-cultural, and economic considerations in a balanced manner. Provide community members with work possibilities, reduce poverty, for-tify local identity, and cultivate a sense of environmental stewardship, nurture the inclination to conserve the environment. Method: This research uses a qualitative, case study-based methodology. Mapping of internal environmental factors (comprising strengths and weaknesses) and exter-nal environmental factors (comprising opportunities and threats) in the coastal regions of Mataram City Lombok. Result: The results of this research revealed that Mataram City's coastal tour-ism offers a wider variety of appealing tourist destinations. An assortment of resources—natural, cultural, and manmade—may serve as an incentive for prospective tourists to visit. Coastal tourism in Mataram City benefits from convenient access and modern amenities. This is attributed to the city's strategic location, which is the epicenter of government and business in the capital of West Nusa Tenggara Province. Furthermore, the promotion and advancement of coastal tourism in Mataram City is bolstered by the collaboration of the tourism pentahelix, an alliance comprised of entities seeking to enhance cultural ties, boost economic engines, and promote environmental preservation. The involvement of local populations in coastal tourism activities inside Mataram City further assists in the advancement of coastal tourism. Contribution: This study contributes to the existing of knowledge by offering recomendation for stakeholders, par-ticularly the public sector, regarding the sustainable development of coastal tourism in Mata-ram City, Lombok Island. Moreover, this research leads to the generation of novel research concepts, such as the growth of urban coastal tourism.